Diseño e implementación de un sistema alternativo capaz de controlar presión, caudal y succión en el oleoducto para RECOPE. - Otero-González, Ingrid (Instituto Tecnológico de Costa Rica, 2001)
The right fuel quantity control that is sent or received by pipeline of Refinadora Costarricense de Petróleo; allows to diminish the losses that are generated when the bombing process of differents products are stoped. This control process is made by MICRO DCITM modular controller and its connection with the valves or with variable frecuency bomb motors. That connection is possible using a programable logical controller. When the modular controller fails the fuel bomb process has to be stoped. The pourpouse of the project was to develop another system that allow the control the process from a computer. This system runs over a monitor platform of industrial process called RSView32, and use the industrial local area network (LAN) DH+ to connect the computer with the programable logical controller of the valve or the variable frecuency bomb motor. Also, the system must to be a mirror of the existing controller, the same options and the same physical presentation. This was achieved at the end of the project. The main activities developed in the project were analisys of valve operation and the study of bomb motors operation; the learning of programable logical controller programation, language and the monitor platform RSView32 and the research of DH+ standart.
Proyecto de Graduación (Bachillerato en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2001
Keywords: Válvulas; Bombeo; Motores; Frecuencia; Control; Programación lógica